2001
DOI: 10.1088/1126-6708/2001/08/024
|View full text |Cite
|
Sign up to set email alerts
|

New cosmological and experimental constraints on the CMSSM

Abstract: We analyze the implications of several recent cosmological and experimental measurements for the mass spectra of the Constrained MSSM (CMSSM). We compute the relic abundance of the neutralino and compare the new cosmologically expected and excluded mass ranges with those ruled out by the final LEP bounds on the lightest chargino and Higgs masses, with those excluded by current experimental values of BR(B → X s γ), and with those favored by the recent measurement of the anomalous magnetic moment of the muon. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(82 citation statements)
references
References 63 publications
(95 reference statements)
5
77
0
Order By: Relevance
“…Initial and early studies [7,8,9,10] were followed by more recent work [11], where it was concluded that current experimental sensitivity is generally comparable with the ranges expected from the neutralino WIMP in the Minimal Supersymmetric Standard Model (MSSM). It is, however, still at least on order of magnitude, or so, above the ranges predicted by recent analyses of the Constrained MSSM (CMSSM) [12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 74%
“…Initial and early studies [7,8,9,10] were followed by more recent work [11], where it was concluded that current experimental sensitivity is generally comparable with the ranges expected from the neutralino WIMP in the Minimal Supersymmetric Standard Model (MSSM). It is, however, still at least on order of magnitude, or so, above the ranges predicted by recent analyses of the Constrained MSSM (CMSSM) [12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 74%
“…Many of these analyses assume that the low-energy soft SUSY-breaking parameters of the MSSM may be extrapolated using the renormalisationgroup equations (RGEs) up to some grand unified theory (GUT) scale, where they are postulated to satisfy some universality conditions. Examples of such models include the constrained MSSM (CMSSM) [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], in which the soft SUSY-breaking mass parameters m 0 and m 1/2 are assumed to be universal at the GUT scale, as are the trilinear parameters A 0 . Other examples include models that relax the universality assumptions for the soft SUSY-breaking contributions to the Higgs masses, the NUHM1 [31][32][33][34] and NUHM2 [35,36] (see also, e.g., Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of gluino coannihilation does not arise in the minimal supersymmetric extension of the Standard Model (MSSM) with the soft supersymmetry-breaking parameters constrained to be universal at the input GUT scale (the CMSSM) [14,[32][33][34][35][36][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92], nor in related models with non-universal Higgs masses [83,84,[93][94][95][96][97][98][99][100][101][102][103][104][105][106]. However, as we discuss in this paper, gluino coannihilation can become important in variants of the MSSM with non-universal gaugino masses, and in variations of pure gravity mediation (PGM) with non-minimal matter content such as additional vector-like supermultiplets [67][68][69].…”
Section: Introductionmentioning
confidence: 99%